(3hUjI GdfHi Udi Gddg Ydjg hSde dGHf Yeg HYd GHfJg dYdi Hf CHj WGdH cQe Gddg hLggs - (3CHh WGgQs
(3ChdgG (B:s
(3bGd CHh WGgQ QVi Gddg Yfg MOKfG Cfg bGd SeYJ QShd Gddg Udi Gddg Ydjg hSde jbhd dYdi Hf CHj WGdH QVi Gddg Yfg CfJ efi HefRdh gGQhf ef ehSi s
(3BNQgG (B:s
(3Hcd fYeI LdjdI jG Ydi GMaX hUjJi ceG MaXJgG Yf LHQjd Yf QH GdYGdejf GfJgi hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3JHUQI GdYfhGf (B:s
(3QhGjI s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B(1280 (3O(B) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs